CONCEPTUAL ASPECTS OF BUSINESS ANALYTICS AS A BASIS OF BANKS FINANCIAL STABILITY - Pylypiv , N.I.; Piatnychuk, I.D.; Boryshkevych , I.I. (The actual problems of regional economy development, 2019)
The article explores the conceptual foundations of banking analytics, which helps to strengthen the financial sustainability of institutions in today's changing and dynamic business environment. The domestic banking sector has been assessed. It was revealed that in 2018 the political situation in the country had no significant impact on the banking sector: deposits from households and businesses have not decreased, banks remain liquid and make all payments without interruption. This indicates a restoration of customer confidence in the banking system. The advantages of using analysts in the process of carrying out their activity are determined. Five areas have been identified in which banks can increase profitability and strengthen their financial sustainability by using business intelligence. It is found that the analysis focuses on understanding what happened, while business analytics focuses on why it happened and what will happen next. Business analytics recognizes patterns in the data, and based on this data helps predict the future. Foreign literature has been studied on the interpretation of the term “analytics”. According to the results of the research, the author's vision of the terms “analytics” and “business analytics” has been formed, which will allow us to apply an empirical approach in carrying out the following scientific researches in order to solve the outlined problems. It has been researched that in Ukraine in banking and other spheres there are already vacancies of analyst (business analyst), to which the following requirements apply: skills in working with software; ability to apply analysis, modeling and to adjust business processes, describe and test business processes; consideration of user requests and advice, reporting periodically or on request, and of course English.